Implementasi Pembelajaran Kitab Aqidatul Awam Dalam Menanamkan Nilai-Nilai Keimanan Santri Putri Di Pondok Pesantren Modern Gondang Wonopringgo Pekalongan Tahun 2023 - Shinta Amelia; Ngarifin Shiqid; Muhammad Saefullah (Institut Nalanda, 2024)
The aim of writing this thesis is to: 1) Examine the idea of teaching lay aqidatul books at the Gondang Wonopringgo Pekalongan Contemporary Islamic Boarding School in order to instill the ideals of faith. 2) to find out how the lay aqidatul book is used to teach religious values to female students at the Gondang Wonopringgo Pekalongan Islamic Boarding School today. 3) to find out the elements that facilitate or hinder the instillation of religious values in lay students at the Gondang Wonopringgo Pekalongan Contemporary Islamic Boarding School through the study of the aqidatul book.This thesis uses a qualitative research methodology with a field research focus. where this kind of descriptive research is carried out. The students, teachers and ustadz of the Gondang Modern Islamic Boarding School were used as research subjects. Interview, observation and documentation techniques were used in data collection techniques. Furthermore, field research and qualitative research were used as data sources. The analytical method used is data analysis, namely examining data collected through research using methodological instruments. Where the data analysis procedures used to collect data are as follows: 1. Data collection, 2. Data reduction, 3. Data display, and 4. Verification (making conclusions).The results of this research show that: 1) The bandongan technique is used to instill religious values in female students at the modern Islamic boarding school Gondang Wonopringgo Pekalongan by teaching lay aqidatul books. 2) At the Gondang Wonopringgo Pekalongan Islamic Boarding School today, the teaching of lay aqidatul books to students is carried out regularly once a week. There are three stages of activities, namely introduction, core and conclusion. 3) Facilities and Infrastructure, the importance of the contents of the Aqidatul Lay book for female students, and teacher motivation for students in improving Aqidatul Lay learning are supporting factors for learning the Aqidatul Lay book in instilling the values of faith in female students at the Gondang Wonopringgo Pekalongan modern Islamic boarding school. The limited time given and the students' understanding of Pegon Arabic in the Yellow Book are the main obstacles for the students at the Kekinian Islamic Boarding School Gondang Wonopringgo Pekalongan studying the lay aqidatul book and upholding the ideals of faith.